Design and Development of a Smart Farm for Broiler Chickens Aged 1 to 10 Days Based on the Internet of Things - Chairil Pratama; Asri, Asri; Daud, Muhammad; Taufiq, Taufiq; Fariadi, Dedi (LPPM Universitas Andalas, 2025)
Broiler chickens have a lower heat tolerance compared to layer chickens, with a normal temperature range of 30 to 33 degrees Celsius. In Desa Sungai Kuruk III, farmers often use traditional methods like burning charcoal and wood to heat the coop, often without considering the ideal temperature standards for broiler chicks aged 1 to 10 days. This method can result in temperatures that are too high or too low, harming the health and growth of the broilers. This research aims to ensure the ideal temperature in broiler coops using smart farm technology based on the Internet of Things (IoT). Through real-time temperature control and monitoring via the web, the coop temperature can be automatically adjusted to remain optimal. This technology allows for more accurate and efficient temperature regulation compared to traditional methods and facilitates remote monitoring of the coop. This research is expected to help broiler farmers in Desa Sungai Kuruk III improve the productivity and welfare of their livestock through the application of modern technology in farm management.